Inverse binding and the status of the Spec. TP position in Polish - Tajsner, Przemysław (Adam Mickiewicz University, 2008)
If the object DP in “inverted” OVS orders in Polish is anaphoric, then there is a question of the satisfaction of anaphoric A-binding in this new position. One type of examples suggests that there is no reconstruction at LF, hence the movement is to an A-position. Other cases seem to indicate the extension of the binding domain. Nonetheless, more facts from Polish point to contrary assumptions. First, object DPs with anaphoric possessives seem to be reconstructed at LF in base positions and there are examples suggesting no extension of the binding domain. The paper offers an account of these perplexingly contradictory facts in terms of the Thematic Hierarchy (Grimshaw 1990) and the specific First Merge properties of “quirky” subjects for some object experiencer verbs (e.g. podobać się) and psych-causative (frightentype) verbs (irytować). Such subjects do enter the derivation in Spec.vP but rather in Spec.VP positions. In conclusion, it is argued that the OVS configurations in Polish do not differ in principle from so-called Dislocation structures, featuring the OSV order (contrary to Baylin 2003 and Witkoś 2007).